2002
DOI: 10.1159/000057603
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Expression of α2(IV) and α5(IV) Chains of Type IV Collagen in Patients with IgA Nephropathy

Abstract: IgA nephropathy (IgAN) frequently accompanies glomerular basement membrane (GBM) alterations. To clarify the compositional changes of the GBM in IgAN, we examined the glomerular expression of α2(IV) and α5(IV) chains of type IV collagen in 36 patients with IgAN. Increased expression of the α2(IV) chain was observed in the expanded mesangium, and there were segmental sclerotic lesions of glomeruli in which the expression of the α5(IV) chain in the GBM was reduced. These lesions were found in 11 out of the 36 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Although the exact molecular mechanisms of renal fibroproliferative diseases are not yet clear, increased synthesis and deposition of types I, III IV, and VI collagens have been detected in chronic progressive fibrotic renal diseases including IgA nephropathy, diabetic nephropathy ( fig. 2) and hypertensive nephrosclerosis [28][29][30]. Morphological changes in various stages of renal diseases range from activation and proliferation of intrarenal cells to severe glomerulosclerosis and tubulointerstitial fibrosis.…”
Section: Renal Fibroproliferative Diseasesmentioning
confidence: 99%
“…Although the exact molecular mechanisms of renal fibroproliferative diseases are not yet clear, increased synthesis and deposition of types I, III IV, and VI collagens have been detected in chronic progressive fibrotic renal diseases including IgA nephropathy, diabetic nephropathy ( fig. 2) and hypertensive nephrosclerosis [28][29][30]. Morphological changes in various stages of renal diseases range from activation and proliferation of intrarenal cells to severe glomerulosclerosis and tubulointerstitial fibrosis.…”
Section: Renal Fibroproliferative Diseasesmentioning
confidence: 99%
“…IgA nephropathy patients without hematuria may have nephrosclerosis or hereditary nephritis with concomitant glomerular IgA deposition, because 4 % of normal persons without urinary abnormalities are reported to have glomerular IgA deposition on postmortem examination after accidental death [7]. Concomitant glomerular IgA deposition has been reported in hereditary nephritis, including thin basement membrane disease [810], mild Alport syndrome [11], focal segmental glomerulosclerosis [12], and complement factor abnormalities [13]. Moreover, the CR rate in patients without proteinuria (mainly hematuria alone) is relatively low, 60.8 % compared to approximately 73.0 % in patients with 0.3–0.69 g/day of urinary protein.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the degree of protein expression, Kim et al [8] noticed an overproduction of col(IV)α5 protein in kidney tissue of 13 patients with diabetic nephropathy, and 21 patients with membranous nephropathy. By contrast, other authors reported a reduction of col(IV)α5, and an increased glomerular expression of col(IV)α2, in patients with IgA nephropathy [9, 10]. …”
Section: Introductionmentioning
confidence: 87%